FACTORS OF INFLUENCEON FOREIGN INVESTMENTIN THE ECONOMY OF UKRAINE: APPROACHES TO CLASSIFICATION - Shevchenko, Liliia (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The publication deals with the issue of classification of factors influencing foreign direct investments. The purpose of the study is to develop a classification of factors and to determine the main factors influencing foreign investments in the economy of Ukraine. The paper contains an overview of studies of significant factors influencing the attraction of foreign direct investments in Ukraine and considers approaches to the classification of factors influencing foreign investments. A detailed analysis of scientists’ approaches to the classification of the factors influencing foreign investments is presented. A review of studies of significant factors influencing the attraction of FDI in Ukraine has shown that the most popular approach to classification is the division of all factors influencing the level of foreign investments demand in any country, on macro- and microeconomic ones. At the same time, macroeconomic factors in turn are detailed by the state and region levels and by the spheres of the economy. It is determined that among the authors there is no unity of views on the classification of factors. Some classifications are narrowly focused. Existing classifications of the factors do not always take into account the processes that cannot be quantified and that are important for foreign investment decision-making. In particular, these include person’s subjective attitude as one of the components of the investment process. Thus, it is necessary to include psychological factors as elements of behavioral economics. Some studies include such factors in the classification, but do not indicate the way of their measuring. Generalization of approaches to the classification of the factors showed that the determining factors for foreign capital attracting to Ukraine remain resource ones and the pace of economic development (as basic economic ones), as well as political, administrative and to a lesser extent financial factors that are specific for Ukraine. The author proposes a new approach to the classification of factors, which unlike others, divides the possible factors in terms of content into three groups: economic, organizational and psychological. There is also an additional "measurement" feature, which allows to divide the factors of each group into qualitative and quantitative ones, which is important for studying their impact using modelling. Further research presupposes dividing the shown factors on the basis of measurement on quantitative and qualitative ones.